Aquaculture feed technology adoption and smallholder household welfare in Ghana. Issue 4 (5th July 2018) - Amankwah, Akuffo; Quagrainie, Kwamena K.
Abstract : This study employs double‐hurdle model and propensity score‐matching techniques to examine the determinants and extent of adoption and the welfare impacts of improved fish feed technology in Ghana using cross‐sectional data of fish‐farming households. The study focuses on the Ashanti, Brong Ahafo, and western regions of Ghana. The results show that the quantity of improved feed used on‐farm is far below what is technically recommended for maximum yield. The analysis provides evidence that the adoption of improved feed technology increases fish income, as well as reduces poverty among fish‐farming households in the study area. In order to spur the adoption and intensity of the technology, complementary factors such as improving education, delivery of extension services and credit facilities, expansion of area under fish farming, and reduction in the price of improved feed are recommended.